Editorial: Rio, Tokyo Paralympic Games and beyond: How to prepare athletes with motor disabilities for peaking - Lepretre, P.-M.; Goosey-Tolfrey, V. L.; Janssen, T. W. J.; Perret, C. (Frontiers in Physiology, 2016)
Finally, all contributors of this special topic provide a descriptive approach of performance, and especially the preparation of athletes with a physical impairment to optimize their exercise performance. Attention has been paid to the accuracy of tools to assess physical (Willems et al.) and physiological responses (Weissland et al.) of athletes with impairment. The motto of Paralympic movement "Spirit in Motion," is also the philosophy of the present compendium in order to present new advances and research findings in the field of applied physiology and biomechanics in Paralymipc sport.